2017
DOI: 10.1002/mnfr.201700252
|View full text |Cite
|
Sign up to set email alerts
|

Dual function of Lactobacillus kefiri DH5 in preventing high‐fat‐diet‐induced obesity: direct reduction of cholesterol and upregulation of PPAR‐α in adipose tissue

Abstract: L. kefiri DH5 exerts anti-obesity effects by direct reduction of cholesterol in the lumen and upregulation of PPAR-α gene in adipose tissues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
71
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(82 citation statements)
references
References 41 publications
4
71
3
Order By: Relevance
“…Therefore, we considered Bacteroides, Prevotella and Akkermansia may be critical contributors for improving lipid metabolism in HFD-fed rats. Intriguingly, the relative abundance of Lactobacillus enhanced remarkably in FMT-HF group rats, which is in contrast with the previous studies that Lactobacillus prevented HFD-induced obesity and hepatic steatosis [50,51]. Nevertheless, our results supported another standpoint that there was a positive correlation between Lactobacillus and obesity [52,53].…”
Section: Discussioncontrasting
confidence: 99%
“…Therefore, we considered Bacteroides, Prevotella and Akkermansia may be critical contributors for improving lipid metabolism in HFD-fed rats. Intriguingly, the relative abundance of Lactobacillus enhanced remarkably in FMT-HF group rats, which is in contrast with the previous studies that Lactobacillus prevented HFD-induced obesity and hepatic steatosis [50,51]. Nevertheless, our results supported another standpoint that there was a positive correlation between Lactobacillus and obesity [52,53].…”
Section: Discussioncontrasting
confidence: 99%
“…L. kefiri is one of the important members of LAB microbiota in milk kefir that was reported to have crucial roles for kefir fermentation as well as for kefiran production (Magalhaes et al ; Magalhães et al ). Several studies also showed the potential probiotic functions of L. kefiri (Kim et al ) and the second dominant presence of this species in traditional kefir grains can be crucial. Similarly, L. kefiranofaciens is another important kefir oriented LAB species that was mainly related to kefiran production (Hamet et al ) and other potential probiotic functions were also discussed for this species (Chen et al ) and we have determined three distinct L. kefiranofaciens strains in this study.…”
Section: Resultsmentioning
confidence: 98%
“…High body weight chickens exhibited higher expression of fat synthesis-related genes in the liver, as well as greater numbers of fat vacuoles in hepatocytes, suggesting stronger fat synthesis in the livers of high body weight chickens. At the same time, the expression of fat catabolism-related genes increased, ultimately promoting the oxidative catabolism of fatty acids, thereby providing energy for the growth and development of chickens [42][43][44]. Abdominal adipose tissue is the main organ of fat synthesis and deposition; the upregulated expression of adipocyte differentiationrelated genes can mediate excessive proliferation and differentiation of adipocytes, causing excessive deposition of fat in animal bodies [45].…”
Section: Discussionmentioning
confidence: 99%
“…Taken together with the fat metabolism results, high body weight chickens store less fat, yet degrade fat to obtain more energy to improve growth [48,49]. Gut microbiota affect fat synthesis and deposition in animals by regulating the expression of fat metabolism-related genes in tissues [44,54,55].…”
Section: Discussionmentioning
confidence: 99%